Understanding the Meaning of the Qur'an, Education, and Entrepreneurship Comprehensively and Their Relationship - Suhairi; Ghozi Mubarok (Values: Jurnal Kajian Islam Multidisiplin, 2025)
The Qur'an not only covers spiritual aspects, but also includes aspects of education and entrepreneurship. In this context, education is not only understood as the transfer of knowledge, but also as a process of forming noble character and morals. On the other hand, entrepreneurship in the Islamic perspective is not only related to economic activities, but also includes ethics and morality in doing business. The concept of the Qur'an is discussed and studied by various scholars with various perspectives that are rich in interpretation by many Muslim scholars and scholars. Understanding of what the Qur'an is can vary among scholars, depending on the theological approach and methodology they use. The relationship between the Qur'an, Education, and Entrepreneurship includes: 1. The Qur'an as a Guide in Education, 2. Education and Entrepreneurship in the Context of Islam, 3. The Teachings of the Qur'an on Entrepreneurship 4. Education in Preparing Muslim Entrepreneurs, 5. Integration of the Values ​​of the Qur'an in Education and Entrepreneurship. This study uses a qualitative approach with a library research method.